Penggunaan Solfegio pada Ekstrakurikuler Drumband di SMP Negeri 8 Padang - Eko Hadi Prasetyo; Jagar Lumban Toruan; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2015)
Abstrak   The purpose of this research was to describe the use of solfegio in drum band  extracurricular  activities  at  SMP  N  8  Padang.  The  activities  covered praticing  rhythm and melody through audio-visual. This was a qualitative research which applied descriptive analysis method. The object of the research was the use of solfegio in drum band extracurricular activities  at  SMP N 8  Padang.  The date were  collected  through  observation, documentation, and library study. The result of the research revealed that, after the students were trained to listen to the rhythm and melody (audio) and read the rhythm and melody (visual): (1) the  students’  knowledge and concept about music increased, (2) the students’ ability to read rhythm notation and melody increased, (3) the students’ skill to use rhythm notation and melody on musical instrument they could play increased, (4) the student’ skill to play music together in presenting the song got better, and (5) the students’ were more excited and self-confident to take part in drum band extracurricular activities.   Keyword: Use, Solfegio, Drum band